Global Increases in Individualism - Santos, Henri C.; Varnum, Michael E. W.; Grossmann, Igor (Psychological Science, 2017)
Individualism appears to have increased over the past several decades, yet most research documenting this shift has been limited to the study of a handful of highly developed countries. Is the world becoming more individualist as a whole? If so, why? To answer these questions, we examined 51 years of data on individualist practices and values across 78 countries. Our findings suggest that individualism is indeed rising in most of the societies we tested. Despite dramatic shifts toward greater individualism around the world, however, cultural differences remain sizable. Moreover, cultural differences are primarily linked to changes in socioeconomic development, and to a lesser extent to shifts in pathogen prevalence and disaster frequency.